Ecological Communities, School Communities: Blurring the Edges - Wiersma, Yolanda (UnderCurrents: Journal of Critical Environmental Studies, 1997)
Ask most children about their favourite subject in school, and they invariably reply "recess". One doesn’t have to think too long about elementary school days to remember the agony of watching the clock tick towards that magical time when the bell rings and a collective sense of relief rises from students and teachers alike. Recess is naturally any child’s favourite subject. It is the only time of the day when children can run around, stretch their legs, talk to friends and play. Recess represents a fleeting freedom that ends each time the bell rings and summons everyone back into the classroom. [...]